2007
DOI: 10.1159/000101367
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and Ciclosporin A in Idiopathic Membranous Nephropathy: Higher Remission Rates of Nephrotic Syndrome and Less Adverse Reactions than after Traditional Treatment with Cytotoxic Drugs

Abstract: Background/Aim: Idiopathic membranous nephropathy, the most common cause of nephrotic syndrome in adults, has been traditionally treated with corticosteroids and cytotoxic drugs. Ciclosporin A (CsA) is used in resistant cases, but also as a first-line treatment, due to the serious side effects of cytotoxic drugs. In this study, the remission rates of nephrotic syndrome and the incidence of side effects of corticosteroids and low CsA doses are compared with those after treatment with cytotoxic drugs. Methods: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
(19 reference statements)
1
19
1
1
Order By: Relevance
“…A comparison of the outcomes of combination therapy using different immunosuppressants showed no significant difference in the overall remission rates among the CTX, MMF, and CsA groups (P > 0.05), and the remission rate was the highest in patients receiving a combination of prednisone and CsA. Renal function before the treatment is an important prognostic factor (Goumenos et al, 2007;Ponticelli and Passerini, 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A comparison of the outcomes of combination therapy using different immunosuppressants showed no significant difference in the overall remission rates among the CTX, MMF, and CsA groups (P > 0.05), and the remission rate was the highest in patients receiving a combination of prednisone and CsA. Renal function before the treatment is an important prognostic factor (Goumenos et al, 2007;Ponticelli and Passerini, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…There are different views about the use of immunosuppressive therapy, and some studies suggest that cytotoxic drugs could decrease the proteinuria and improve the clinical remission rate in patients with membranous nephropathy. Recently, some studies showed that administration of the calcineurin inhibitor cyclosporine A (CsA) at conventional doses (3-5 mg·kg -1 ·day -1 ) significantly improved the prognosis of NS patients with worsened renal functions but was associated with complications such as hepatonephric dysfunction and infections (Goumenos et al, 2007;Ponticelli and Passerini, 2010). Further, the administration of CsA alone for the treatment of membranous nephropathy explored previously was partially effective.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients in the treated group progressed to the end stage (11% versus 50%, respectively). Goumenos et al (20) reported that during a mean follow-up of 48 months, there were no differences in rates of doubling of serum creatinine between the cyclosporine-treated patients than among those taking alkylating agents. This study showed that treatment with cyclosporine 3-6mg/kg/d or tacrolimus 0.05mg/kg/d induces remission in IMN patients over 3 months and 6 months after dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Goumenos et al attempted to address this issue by comparing the outcomes of patients who were treated with a 6-month Ponticelli protocol (steroids plus chlorambucil or cyclophosphamide; n=31) with those treated with cyclosporine for 2 years plus steroids (n=46). 59 The use of different therapeutic regimens in the two groups reflects institutional treatment preferences over a 10-year period. Baseline characteristics of the groups were similar.…”
Section: Cnismentioning
confidence: 99%